KEANEKARAGAMAN JENIS PLANKTON DI DANAU BUYAN KABUPATEN BULELENG – BALI - Muksin, I Ketut (Bumi Lestari; Vol 3 No 2)
A study on plankton diversity in Lake Buyan is very important to be undertaken. Thisis related to the fact that it is frequently mentioned that its condition is getting worse, itscapacity decreased because of sedimentation and its fish density is decreasing.Since the surrounding of the lake has been mostly utilized for agricultural activities,and settlement is getting dense there, it is likely that pollutant as well as untreated dischargedwater has flushed into the lake.Results of the study showed that there were 33 plankton species there prior toEichornia being cleared from the lake. The species richness decreased to 26 after clearing.
Keywords: sedimentation, discharged water, species diversity